Analisis Nilai Tambah CCO (Crude Coconut Oil) di Rumah Produksi Mayang Sari Desa Nitakloang, Kecamatan Nita, Kabupaten Sikka - Yoseph Yakob Da Rato; Maria Emerensiana (Jurnal Ilmiah Wahana Pendidikan, 2022)
Value added is the value added of a commodity because it undergoes a process of processing, transporting or storing in a production. In the processing process, value added is defined as the difference between the value of the product and the price of raw materials and other inputs, excluding labor, while this margin is covered by the components of the production factors used, namely labor, other inputs and the remuneration of processing entrepreneurs. Smart CCO Production Rotat is one of the agro-industries engaged in producing coconut oil. The sample used in this study was the Mayang Sari Production House, Nitakloang Village, which became one of the CCO production house businesses under the auspices of PT. Smart Asia- Smart CCO Production Rotat in Sikka District area. This study aims to determine the added value of CCO (Crude Coconut Oil) production produced by the Mayang Sari Production House, Nitakloang Village, Nita District, Sikka Regency. The analysis used uses value-added analysis with the Hayami method. The added value generated from the processing of coconut milk into CCO (Crude Coconut Oil) at the Mayang Sari Production House, Nitakloang Village, Nita District, Sikka Regency is IDR 219,550.00 / one production process with a value-added ratio of 90.45%.